Peran regulasi emosi terhadap kecenderungan self injury pada wanita di masa quarter life crisis (SUKMA : Jurnal Penelitian Psikologi, 2023)
This research aims to determine the relationship between emotional regulation and the tendency for self-injury in women during the quarter life crisis. This research used quantitative research with a total of 202 female subjects. The sampling technique uses a purposive sampling technique. The measuring tool used is a scale of self-injury and emotional regulation in women during the quarter life crisis. Hypothesis testing was carried out using the Spearman's Rho correlation formula assisted by SPSS 20 for Windows. The Spearman's Rho correlation coefficient result is -0.858 with a significance level of p = 0.000 (p < 0.05), which means there is a negative relationship between emotional regulation and the tendency for self-injury in women during the quarter life crisis. This means that the higher the emotional regulation, the lower the tendency for self-injury, and vice versa, the lower the emotional regulation, the higher the tendency for self-injury in women during the quarter life crisis. This study has an R Square of 0.821 or 82.1%, which means that 82.1% of the tendency for self-injury is influenced by emotional regulation and 18.9% is influenced by other factors.